Extending Heterogeneous Applications to Remote Co-processors with rOpenCL - Alves, Rui; Rufino, José (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2020)
In heterogeneous computing systems, general purpose CPUs are coupled with co-processors of different architectures, like GPUs and FPGAs. Applications may take advantage of this heterogeneous device ensemble to accelerate execution. However, developing heterogeneous applications requires specific programming models, under which applications unfold into code components targeting different computing devices. OpenCL is one of the main programming models for heterogeneous applications, set apart from others due to its openness, vendor independence and support for different co-processors. In the original OpenCL application model, a heterogeneous application starts in a certain host node, and then resorts to the local co-processors attached to that host. Therefore, co-processors at other nodes, networked with the host node, are inaccessible and cannot be used to accelerate the application. rOpenCL (remote OpenCL) overcomes this limitation for a significant set of the OpenCL 1.2 API, offering OpenCL applications transparent access to remote devices through a TPC/IP based network. This paper presents the architecture and the most relevant implementation details of rOpenCL, together with the results of a preliminary set of reference benchmarks. These prove the stability of the current prototype and show that, in many scenarios, the network overhead is smaller than expected.